2019
DOI: 10.1530/jme-18-0150
|View full text |Cite
|
Sign up to set email alerts
|

Applying mass spectrometric methods to study androgen biosynthesis and metabolism in prostate cancer

Abstract: Recent development of gas chromatography and liquid chromatography-tandem mass spectrometry (GC-MS/MS, LC-MS/MS) has provided novel tools to define sex steroid concentrations. These new methods overcome several of the problems associated with immunoassays for sex steroids. With the novel MS-based applications we are now able to measure small concentrations of the steroid hormones reliably and with high accuracy in both body fluids and tissue homogenates. The sensitivity of the tandem mass spectrometry assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Also, several of these studies indicated that the sexual dimorphism in serum T levels is attenuated in GF mice (33,49,50). These studies used less specific immunoassay-based techniques for analysis of serum T levels, with known limitations in the lower concentration range (26,30), and different mouse strains, most probably with different GM compositions, at different ages compared with the present study. Interestingly, our study demonstrated elevated tissue DHT levels in the liver and seminal vesicles of male GF mice, with a similar trend in the thymus.…”
Section: Discussionmentioning
confidence: 75%
“…Also, several of these studies indicated that the sexual dimorphism in serum T levels is attenuated in GF mice (33,49,50). These studies used less specific immunoassay-based techniques for analysis of serum T levels, with known limitations in the lower concentration range (26,30), and different mouse strains, most probably with different GM compositions, at different ages compared with the present study. Interestingly, our study demonstrated elevated tissue DHT levels in the liver and seminal vesicles of male GF mice, with a similar trend in the thymus.…”
Section: Discussionmentioning
confidence: 75%
“…The androgen metabolic pathway is important in androgen synthesis and metabolism. It has been demonstrated that the abnormal function of the androgen metabolic pathway plays key role in the occurrence of CRPC [29]. The androgen metabolic pathway consists of several components, which include cytochromes P450 (CYPs) [30].CYPs are one of the largest and most diverse superfamily of enzymes [6].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Thus, further studies are needed using, for example, a gas chromatography-tandem mass spectrometry, which has been applied for detecting steroid hormones at low concentrations, to detect the upregulation of potential ERβ ligands in the prostate. 29 Second, we evaluated the mRNA expression levels of only a few cytokines, but not underlying inflammatory cascades in the prostate with or without dutasteride administration. While additional studies will be required to fully explain the anti-inflammatory effects of dutasteride in the prostate, the impact of this androgen metabolism inhibitor on the opposing actions of ERα and ERβ, as implicated by our results, will clearly be an important mechanism to decipher.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen metabolites, such as Δ5‐diol or dehydroepiandrosterone, a precursor of ERβ ligands reportedly stimulate ERβ 27,28 . Thus, further studies are needed using, for example, a gas chromatography‐tandem mass spectrometry, which has been applied for detecting steroid hormones at low concentrations, to detect the upregulation of potential ERβ ligands in the prostate 29 . Second, we evaluated the mRNA expression levels of only a few cytokines, but not underlying inflammatory cascades in the prostate with or without dutasteride administration.…”
Section: Discussionmentioning
confidence: 99%